12c-4=12

Simple and best practice solution for 12c-4=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12c-4=12 equation:


Simplifying
12c + -4 = 12

Reorder the terms:
-4 + 12c = 12

Solving
-4 + 12c = 12

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 12c = 12 + 4

Combine like terms: -4 + 4 = 0
0 + 12c = 12 + 4
12c = 12 + 4

Combine like terms: 12 + 4 = 16
12c = 16

Divide each side by '12'.
c = 1.333333333

Simplifying
c = 1.333333333

See similar equations:

| .30(6)+.05x=.10(12+x) | | 5(4.56)+=-5 | | 19x^3-17x^2-2x=0 | | 1.5x^2-12x-37.5=0 | | 5x+50=250 | | 32-4x=-5(6x+4)-5(-8-5x) | | 12m-9=4m+5 | | 8x+8+7x-4= | | 3(y+4)=4(y-2) | | 1x+-3=-10 | | 150m-125m+33600=35000-150 | | 2.50(x+15.00)=662.50 | | 5(s+3)=45 | | x=2+-0.5X | | 6(2+c)=5(c-8) | | 12+3m= | | u^2+10+21=0 | | 2.50(x+15.00)=412.50 | | 2(x+1)=6-X | | 25=p/6+(-19) | | -x^2+7x+30=0 | | 4(10b+7)-6b= | | 4(2c+3)-2=2(4c+6) | | 5d-15= | | 33-8x=13+12x | | 2x-2=2(x+5) | | 5.7x-17.3+5.3x=6.4+12x | | 3x=9(x-5) | | 10a+2a= | | f(-4)=3x^2-6x+5 | | 36-11x=20+5x | | 3(x+2)=6x-1 |

Equations solver categories